Management of Complications of Injectable Silicone - Hexsel, Doris; de Morais, Marina Resener (Facial Plastic Surgery, 2014)
Soft tissue augmentation is a common procedure, and a wide variety of injectable fillers are used. Liquid injectable silicone (LIS) was the first highly popularized injectable filler. LIS is a permanent filler and can be used in the correction of facial furrows and wrinkles. Some complications are inherent to the procedure and can resolve spontaneously, such as redness, swelling, and immediate hypersensitivity reactions. Unintended reactions, such as granulomas, infections, vascular occlusion, can also follow the treatment with LIS and may appear several years after the injections. These can be difficult to manage, show little or no tendency to spontaneous resolutions, and rarely resolve completely. Injecting physicians must be aware of these potential complications caused by LIS because early medical care and treatment, including psychological support for these patients, can minimize the consequences for patients and physicians, and may also help obtaining better outcomes when treating complications.
Keywords: dermal fillers; injectable augmentation; silicone; complications